Gaining Traction in Research Data Management Support: A Case Study - Donna L. O'Malley (Journal of eScience Librarianship, 2014)
With the implementation of an institutional repository, librarians at the University of Vermont (UVM) began receiving inquiries about data management. In an effort to explore research data management roles for librarians at UVM the author led workshops based on Module One of the New England Collaborative Data Management Curriculum (NECDMC) with two audiences. In addition, the author consulted with faculty and staff from around the university to ascertain their support of research data management and integrate that information into the workshops. The first workshop was directed at UVM librarians and resulted in an understanding of their willingness to engage with research data management patron services. The second workshop was conducted for students and faculty. It built upon the first workshop and, in addition, experimented with a sixty-minute version of the NECDMC module. This second workshop will be added to an existing series of Dana Library workshops for graduate students and early-career researchers in fall 2014.